2021
DOI: 10.1039/d0ce01714k
|View full text |Cite
|
Sign up to set email alerts
|

Contact map based crystal structure prediction using global optimization

Abstract: Crystal structure prediction is now playing an increasingly important role in the discovery of new materials or crystal engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…This method is conceptually similar to our decoder, but it requires additional force data and can only be applied to 1-2 elements due to the exponentially increased data need for more elements. Remotely related works include generating contact maps from chemical compositions Yang et al, 2021) and building generative models only for compositions Pathak et al, 2020;Dan et al, 2020).…”
Section: Related Workmentioning
confidence: 99%
“…This method is conceptually similar to our decoder, but it requires additional force data and can only be applied to 1-2 elements due to the exponentially increased data need for more elements. Remotely related works include generating contact maps from chemical compositions Yang et al, 2021) and building generative models only for compositions Pathak et al, 2020;Dan et al, 2020).…”
Section: Related Workmentioning
confidence: 99%
“…In our previous work [4], the crystal structure prediction problem can be mapped to two related problems: 1) prediction of the contact map of atoms; 2) the atomic coordinate reconstruction from the contact map using global optimization algorithms. We have applied both genetic algorithms and differential evolution algorithms [37] for the coordinate reconstruction.…”
Section: B Age-fitness Based Multi-objective Genetic Algorithm For Cr...mentioning
confidence: 99%
“…The discovery and development of new materials are fundamental to the progress of technology. There are several promising approaches for exploring new materials including crystal structure predictions [1][2][3][4], generative machine learning models [5][6][7][8], inverse materials design [5,9], and first-principles [10][11][12] calculation based structural tinkering. Materials Genome Initiative attempts to use data-driven methods [13][14][15] to help discover new material science research paradigms and accelerate the design and exploration of new materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latest approach uses deep learning to predict the contact maps or distance matrix, which can then be used to reconstruct the full 3D protein structure with a high accuracy . In our prior work, we have shown that given a crystal’s space group, its lattice constants, and the contact map, all of which can be predicted, we can reconstruct the crystal structure atom coordinates using global optimization algorithms such as genetic algorithms (GAs), particle swarm optimization, or Bayesian optimization. However, it is known that pairwise distances between atoms within a crystal structure usually are conserved across different compounds, so that machine learning models can be built to predict the distance matrix of a given composition.…”
Section: Introductionmentioning
confidence: 99%